Εκφοβισμός και θυματοποίηση στην προεφηβική και πρώτη εφηβική ηλικία: Συχνότητα και διαφορές ηλικίας και φύλου - Γαλανάκη, Ε.; Ε Αμανάκη (Πρακτικά του 6ου Πανελλήνιου Συνεδρίου της Παιδαγωγικής Εταιρείας Ελλάδος «Ελληνική Παιδαγωγική και Εκπαιδευτική Έρευνα», 2009)
The aim of this study was to examine the prevalence of bullying/victimization during preadolescence and early adolescence in Greece, in relation to age and gender. Participants were 655 fifth, seventh, eighth and ninth graders from Athenian schools. They completed the Revised Olweus Bully/Victim Questionnaire (Olweus, 2006). Data showed a high prevalence of bullying and victimization, with verbal bullying and social exclusion as the most frequent forms. Self-reported victimization decreased with age, with the exception of electronic victimization which increased, whereas self-reported verbal, sexual, and electronic bullying increased with age. Boys preferred verbal, physical, racial, sexual, and electronic bullying significantly more than girls. More boys felt bullied for racial reasons than girls, whereas girls felt more sexually victimized than boys. Results are discussed in the framework of the existing literature on bullying and victimization, and some implications for interventions are presented.